An annotated checklist of palms at Ulu Endau Johore Malaysia - Dransfield, John; Kiew, Ruth (Malaysian Nature Society, 1987)
A checklist of 71 palm species in 21 genera recorded from Ulu Endau, Johore is given together with notes on their ecology. More than half the species are rattans. Three species are endemic to the area: Calamus endauensis, Livistona endauensis and Salacca minuta. Licuala kiahii, L. lanuginosa and Nenga grandiflora are endemic to Johore. The fact that Ulu Endau houses about a third of Peninsular Malaysia's total palm flora, as well as several endemic species, underlines its importance as a conservation area